Effect Of The Microchannel Configurations On Mixing Performance - Yunus, Nur Fatihah (Universiti Sains Malaysia, 2017)
With the technology development in this decade, microchannel technology has became one of the most important tool in chemical synthesis because of its benefit in providing greatly enhanced mixing in short time. It is also widely known because of its ability in performing the process intensification which significantly catching up with the trend in the industry. With the abilities in reducing the size, low cost, high productivity and enhance safety, make microreactor as one of those useful tools to the future of chemical engineering. The mixing quality in the microfluidic device is further investigated in order to improve the one that have been studied by other authors. In this study, three-dimensional Computational Fluid Dynamics (CFD) model with circular cross section have been developed to investigate the mixing quality in different microchannel configurations with different inlet velocity, diffusion coefficient and type of meshing. The results have shown that inlet velocity has a great impact on the mixing performance. The faster mixing performance can be seen when low inlet velocity and high diffusion coefficient have been used. The fine type of meshing shows slower mixing quality than normal type of meshing because it takes a lot of time even though it is better in solving the problem in CFD software. Y-shaped microchannel shows better mixing quality than T-shaped and Arrow-shaped microchannels.